Rasio Aktivitas dan Leverage terhadap Financial Distress Perusahaan subsektor Food and Beverage (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to examine the effect of inventory turnover (activity ratio) and Debt to Asset Ratio (leverage ratio) on financial distress conditions, measured using the Altman Z-score model. The research focuses on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined using a purposive sampling method based on specific criteria to obtain consistent data throughout the observation period. A total of 25 observations were analyzed using the multiple linear regression method. To address the violation of the residual normality assumption in a small sample size, the model's parameter estimates were adjusted using the HC3-type Robust Standard Error approach, while the presence of autocorrelation  was acknowledged as a limitation of the pooled OLS model. The partial test results indicate that inventory turnover does not have a significant effect on financial distress , whereas the Debt to Asset Ratio has a significant negative effect (p < 0.001). Together, these two variables contribute 80.3% to explaining the variation in companies' financial conditions. This research confirms that a high proportion of debt serves as a primary determinant increasing the risk of corporate financial distress. Consequently, management is advised to optimize capital structure efficiency and mitigate solvency risks.